Psychological Factors and its Effects on Nepalese Athletes - Acharya, Ashish (HPE Forum, 2025)
This study aimed to investigate the psychological factors affecting sports performance. Five variables of psychological factors were included in the study: Motivation, Dedication, Stress and Anxiety, Satisfaction, Group Dynamics as independent variables. On the other hand, Sports performance as an indicator is its dependent variable. Systematic random sampling was applied as a sampling technique. Population of this study comprised the Athletes form different sports of Nepal. 230 respondents were distributed questionnaires. Only (200) responses were valid for the test. Descriptive and analytical methods was used for analysis. Study has shown that attributes such as Motivation, Dedication and Satisfaction have a significant positive correlation relationship with Sports performance of Nepalese athletes. Improvement in such factors will help in developing positive mindset towards desired Sporting goal on athletes of Nepal and will help in improving the performance of Nepalese athletes. Stress and Anxiety has Negative correlation with sports performance. And Group dynamics has no significant relationship with dependent variables. As such, the researcher recommends Sports associations, Coaches and Athletes of Nepal have give specific attention on psychological part of sports which will help in performance of an athletes. This research also concludes that athletes having positive mentality or without any mental pressure can give a better performance.